The characteristics of political relations between the Arab and the Persian during the reign of the sassane kings “Ardashir the first, shahbour the first, shahbour the second, Bahram the fifth; kisra Anushrwan and kisrah Abruis” as amodel (Journal of the College of Education for Women, 2019)
This paper depends on sheding some litgt on the characteristics of politicalrelations between the arab and the Persian during the reign of sassane kings."Ardashir the first, shahbour the first, shahbour the second, Bahram the fifth; kisraAnushrwan and kisrah abruis"And who rulled the Persian before the Islamic conquest and were adopted in this studymas a model. It was possible to get some information from invaluable refereces in order toarrive at a clear image as regards the nature of these relations. These relations weredifferently political according to the circumstances of ruling, interests and the personalityof those kings.